(3GdCdajI aj abg GdUdGI GdjhejIs - (3GdYGedj GdfHWj GdLRjfi, TeS GdOjf, GdTgjO GdChd, eMeO Hf eci Hf eMeO Hf MGeO, J (B786 (3g`s ((3MjOQ Ydjs)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf(B... (3CeG HYO agPg QSGdI hLjRI aj aQV GdUdGI(B...s
(3BNQgG (B:s
(3hdh CWdb GdbVGA Ydi GdWhGa hGdLfGRI aLGR, hcPG EfPGQ GdeWdb(B. (3JeJ GdQSGdIs
(3JHUQI GdeDda (B:s
(3GdTgjO GdChds
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: (3L(B7(3, U(B109s
(3EjVGM Gdecfhf(B: (3L(B1(3, U(B559s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3abg GdePGgH GdCNQis